Iparosodás agrártérségben: a gyáripar kialakulása Nagykanizsán a 19-20. század fordulóján - Kaposi, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
This study deals with the industrialisation of the largest market centre of the Southwest Transdanubian Region of Hungary. Nagykanizsa was an agrarian town for a long time; however, a quick increase in trade begun from the 1830s. The industry showed small plant traits. The industrialisation started in the 1880s in this region too. Newness was the mass producing mechanised manufacturing. The manufacturing came into existence in three ways. The first case was when the already existing small plants were developed to factories due to the good trading opportunities. In the second case traders and craftsmen established businesses based on local innovations; therefore, new industries were acclimatised. And the third case was the creation of corporations which presumed large amount of capital. Due to the development, the industry became the most important sector in the structure of the economy of the town before the World War I.